The review of clinical use of current anti-VEGF injections in retinopathy of prematurity [Prematüre retinopatisinde güncel anti-VEGF enjeksiyonu klinik uygulamalarının gözden geçirilmesi] - (:unkn) unknown (Gazi Eye Foundation, 2015)
Retinopathy of prematurity (ROP) is one of the major causes of visual loss in childhood in developed and developing countries. With the convenient screening and treatment methods, blindness due to ROP has significantly reduced. In Turkey, the incidence of ROP has been gradually increasing upon improved conditions of neonatal intensive care units. Conventional laser retinal photoablation therapy has provided effective results though it is inadequate in certain cases such as posterior ROP, small pupil and hazy ocular media. Additionally, laser photocoagulation destructs peripheral retina stopping the physiologic extension of normal blood vessels as well as abnormal ones. The intravitreal administration of anti-VEGF (vascular endothelial growth factor) injection is becoming more popular in the treatment of severe posterior ROP in the last few years. This article reviews the effectiveness of anti-VEGF applications in the treatment of ROP. © 2019 Gazi Eye Foundation. All Rights Reserved.
Keywords: Anti-VEGF treatments; Intravitreal injection; Retinopathy of prematurity